The Role of Guidance and Counseling Teachers in Preparing Students for The Society 5.0 Era - Nasution, Salsabila; Jamaris, Jamaris; Solfema, Solfema; Almizri, Wahyu (Guidance and Counseling Study Program, Pattimura University, 2023)
The development of today's human era will enter the era of society 5.0. In this era, technology and humans are made the most important center for the development of life. Students in the era of society 5.0 are required to be able to develop soft skills and abilities so that they become material in dealing with changes and human development. The purpose of this article is to determine the role of counseling teachers for student readiness in entering the era of society 5.0 by using qualitative research methods in a systematic review used to synthesize (summarize) the results of research that are descriptive qualitative in nature with sources from several international, national, and international journals. a book that will produce information in the form of notes and data in a descriptive form based on literature studies through references relevant to research. As for the results of this study, students have challenges when entering the era of society 5.0, one of the challenges is that students must be able to develop and improve their abilities in facing the era of society 5.0. In developing and improving the abilities of students. Counseling guidance teachers can provide counseling guidance services that are innovative, creative and up-to-date in accordance with the needs of students which are adapted to the times.